2017
DOI: 10.1016/j.tim.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Interactions in the Microbiome: A Network Perspective

Abstract: Microbiota are now widely recognized as being central players in the health of all organisms and ecosystems, and subsequently have been the subject of intense study. However, analyzing and converting microbiome data into meaningful biological insights remain very challenging. In this review, we highlight recent advances in network theory and their applicability to microbiome research. We discuss emerging graph theoretical concepts and approaches used in other research disciplines and demonstrate how they are w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
497
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(503 citation statements)
references
References 81 publications
4
497
0
2
Order By: Relevance
“…Additionally, these features indicated that the fungi displayed small-world behaviour. In a small-world network, most OTUs are accessible to every other OTU through a relatively short path (Layeghifard, Hwang, & Guttman, 2017). The degrees for the bacterial network were distributed according to power-law distributions (Fig.…”
Section: Distinct Co-occurrence Patterns Of Soil Bacteria and Fungimentioning
confidence: 99%
“…Additionally, these features indicated that the fungi displayed small-world behaviour. In a small-world network, most OTUs are accessible to every other OTU through a relatively short path (Layeghifard, Hwang, & Guttman, 2017). The degrees for the bacterial network were distributed according to power-law distributions (Fig.…”
Section: Distinct Co-occurrence Patterns Of Soil Bacteria and Fungimentioning
confidence: 99%
“…Network inference techniques are increasingly employed to decipher the relationships among microbes (Faust et al, 2015). These techniques range from simple pairwise Pearson or Spearman correlation measures, to more complex multiple regression and Gaussian graphical models (Zhou et al, 2010;Van den Bergh et al, 2012;Layeghifard et al, 2017). The application of network theory to microbiome studies can be used to model the co-occurrence of microorganisms, find microbial relationships essential for community assembly or stability and deduce the influence of various interactions on the host health (Layeghifard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques range from simple pairwise Pearson or Spearman correlation measures, to more complex multiple regression and Gaussian graphical models (Zhou et al, 2010;Van den Bergh et al, 2012;Layeghifard et al, 2017). The application of network theory to microbiome studies can be used to model the co-occurrence of microorganisms, find microbial relationships essential for community assembly or stability and deduce the influence of various interactions on the host health (Layeghifard et al, 2017). Long-term inorganic fertilization can increase the availability of soil nutrients and thus weaken the stability of the microbial network structure; for example, microbial networks in soils with applications of N-P-K fertilizer become sparse and divergent (Li et al, 2017;Wang et al, 2017a,b).…”
Section: Introductionmentioning
confidence: 99%
“…From protein-protein interaction prediction [3] to the identification of candidate disease genes to drug repositioning [4] or very recent applications on microbiology [5], it seems to be clear that inference on graph or network data structures can be effective for the purpose of finding relations between entities that interact in such ways [1]. These in silico predictions allow researchers to reduce the search space to focus on a small set of entities that are more likely to be related to the entities of interest.…”
Section: Resultsmentioning
confidence: 99%